Dagestan national clothes as an attribute of rural everyday life. 1920–1960s - Madina Magomedovna Amirkhanova (Вестник Майкопского государственного технологического университета)
The relevance of the research topic is due to the growing interest in everyday culture. A suit is one of the most necessary elements of everyday life for a person, constantly present in material culture at all times. In national clothes, the values of the time, consonant with the era, are objectively fixed.The national costume is comprehensively considered in the context of socio-historical processes, using the principle of historicism and interdisciplinary, comparative, historical, logical, problem-chronological methods. The purpose of the research is to show the spatial and temporal processes of distribution, development of traditional clothes of Dagestan, general and special in cut, the way of wearing clothes among different nationalities, to analyze the transformation of the national costume in the specified chronological framework. Scientific novelty is seen in the fact that the analysis of diverse sources has made it possible to identify regional features of the national clothes of the highlanders: the impact of social and economic transformations in the Republic on changes in national clothes, its unification. The factors accelerating these processes have been determined. The author concludes that during the period under review, the transformation of the national clothes of Dagestan was greatly influenced by fundamental social and economic changes in the Dagestan village: the deployment of collectivization, resettlement. The theoretical and practical significance of the work is determined by the expansion of scientific knowledge about the national clothes of the highlanders, as an important component of everyday life, reflecting the specifics of the people.